2012
DOI: 10.1073/pnas.1201552109
|View full text |Cite
|
Sign up to set email alerts
|

Nanoelectrodes for determination of reactive oxygen and nitrogen species inside murine macrophages

Abstract: Reactive oxygen and nitrogen species (ROS and RNS) produced by macrophages are essential for protecting a human body against bacteria and viruses. Micrometer-sized electrodes coated with Pt black have previously been used for selective and sensitive detection of ROS and RNS in biological systems. To determine ROS and RNS inside macrophages, one needs smaller (i.e., nanometer-sized) sensors. In this article, the methodologies have been extended to the fabrication and characterization of Pt/Pt black nanoelectrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
169
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(176 citation statements)
references
References 25 publications
7
169
0
Order By: Relevance
“…Platinized nanoelectrodes were recently used for the intra-cellular detection of Reactive Oxygen and Nitrogen species (ROS/RNS) species inside murine macrophages. 18 In that work, despite the nanometer dimension of the electro-active area, the outer glass coating was of several hundreds of nanometers. The small outer diameter of our nanoelectrodes allowed us to perform electrochemical measurement both in tissue and in cultured cells at the single-cell level.…”
Section: Resultsmentioning
confidence: 93%
“…Platinized nanoelectrodes were recently used for the intra-cellular detection of Reactive Oxygen and Nitrogen species (ROS/RNS) species inside murine macrophages. 18 In that work, despite the nanometer dimension of the electro-active area, the outer glass coating was of several hundreds of nanometers. The small outer diameter of our nanoelectrodes allowed us to perform electrochemical measurement both in tissue and in cultured cells at the single-cell level.…”
Section: Resultsmentioning
confidence: 93%
“…The successful amperometric detection of dopamine and other catecholamines in chromaffin cells has been reported by Mosharov et al 22 With the help of micrometer-and submicrometer-sized Pt electrodes the production and release of reactive oxygen and nitrogen species (ROS, RNS) can be amperometrically locally resolved and detected. 23 For small viologens it has been shown that there is no interaction with the predominant NADH/NAD + redox system in the cytosol. Viologen dendrimers reveal the possibility to electrochemically elucidate not only the DNA release of dendriplexes within a mammalian cell, but also the mechanism and location of drug release whether the release occurs in the cytosol or near the cell nucleus (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers must investigate the reactivity of a protein with its physiological partners to understand its role in cellular pathways; concentration measurements alone could be misleading, because the local environment of a protein can drastically alter its activity. Emerging capillary micro-/nanofabrication technologies allow the chemical reactivity of the target species to be investigated (3,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Allbritton and coworkers (11,12) embarked on the development of this technology and used capillary electrophoresis to analyze intracellular kinase activity.…”
mentioning
confidence: 99%